Needs of family caregivers in home care for older adults - Carla Cristiane Becker Kottwitz Bierhals; Naiana Oliveira dos Santos; Fernanda Laís Fengler; Kamila Dellamora Raubustt; Dorothy Anne Forbes; Lisiane Manganelli Girardi Paskulin
ABSTRACT Objective: to reveal the felt and normative needs of primary family caregivers when providing instrumental support to older adults enrolled in a Home Care Program in a Primary Health Service in the South of Brazil. Methods: using Bradshaw's taxonomy of needs to explore the caregiver's felt needs (stated needs) and normative needs (defined by professionals), a mixed exploratory study was conducted in three steps: Descriptive quantitative phase with 39 older adults and their caregiver, using a data sheet based on patient records; Qualitative exploratory phase that included 21 caregiver interviews, analyzed by content analysis; Systematic observation, using an observation guide with 16 caregivers, analyzed by descriptive statistics. Results: the felt needs were related to information about instrumental support activities and subjective aspects of care. Caregivers presented more normative needs related to medications care. Conclusion: understanding caregivers' needs allows nurses to plan interventions based on their particularities.